Skuteczne szkolenie pracowników w świetle wyników badań empirycznych - Janiak-Rejno, Iwona (The effectiveness of employees' training in the light of empirical research outcome, 2006)
The article presents the results of the author’s scientific research. The main purpose is the identification, analyzing and evaluating determinates which have influence on effectiveness of employees’ training. The base research was conducted in about eighty Polish companies, differ on their number of employees, the source of capital and the branch of activities. Moreover, the author conducted additionally research among the professional trainers to know their opinion on this subject. Finally, these factors were divided on three groups: very important, less important and not important.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 167-182